Implementation of Hierarchical Clustering for Grouping Economic Development Indicators in Central Java Province: Penggunaan Clustering Hierarki Untuk Pengelompokan Indikator Pembangunan Ekonomi di Provinsi Jawa Tengah - Salmaa; Yusrisma Asyfani; Indah Manfaati Nur (Department of Sains Data UNIMUS Universitas Muhammadiyah Semarang, 2025)
In the midst of global economic shifts, the economy in Indonesia must continue to improve. To help economic recovery after the contraction caused by the COVID-19 pandemic, the Indonesian government has implemented various policies. One way is through the process of increasing per capita income over a long period of time, known as economic development, provided that the number of people living below the absolute poverty line does not increase and income distribution does not decrease. Other efforts can be made by analyzing economic development indicators. One method that can be used is hierarchical cluster analysis to group economic development indicators in Central Java province. Average linkage is used as an approach method after carrying out correlation analysis of the five approaches in hierarchical analysis because the correlation value is the highest. From this analysis two clusters were produced with the first cluster having higher characteristic values compared to the second cluster.